(untitled) (Revista Espinhaço, 2019)
With continental dimensions, Brazil contains heterogeneous rural spaces, where diverse forms of social, economic and access to land organization are found. These, in turn, are related to the country´s colonization and land policy that benefited one category over another. This article aims to present a synthesis of the Brazilian rural space diversity, based on a bibliographical review of selected texts on the theme. The variety of rural spaces in Brazil found in contemporaneity brings relatively sharp ruralities in the way people establish their mode of producing space and reproducing themselves. In diverse rural contexts, with different characteristics and lifestyles, economic and socio-cultural relations are constituted in observance of the peculiarities of the place, whose relations are responsible for shaping the space, at the same time that they are shaped by the place in which they are established.